Making Ant Sugar from Brown Sugar for Partner Groups in Paddinding Village, Takalar Regency, South Sulawesi Province - Niniek F. Lantara; Aryati Arfah (Manunggal Halim Jaya, 2022)
The Social Service program to be developed is Ant Sugar Manufacturing in Takalar regency. The manufacture of ant sugar uses brown sugar as raw material. Apart from being sweet, ant sugar has a distinctive aroma and is more durable. This ant sugar can be made using simple technology and equipment, so it is very easy to develop by the Paddingnging Village Partner Group, Sandrobone District, Takalar Regency to become new entrepreneurs who will be able to increase income/income, as well as improve the community's economy. This ant sugar product has the opportunity to be marketed in stores because it is generally liked by the public and can improve public health as well as has a long shelf life and is practical in its use. To solve this problem requires knowledge, skills and mastery of technology, especially Appropriate Technology or technology that is easily applied in society. Ant Sugar product processing can be done using simple technology so it is easy to develop.